2014
DOI: 10.1007/s00455-014-9527-8
|View full text |Cite
|
Sign up to set email alerts
|

Carers’ Experiences of Dysphagia in People Treated for Head and Neck Cancer: A Qualitative Study

Abstract: The implication of dysphagia for people treated nonsurgically for head and neck cancer (HNC) and its detrimental effects on functioning and quality of life has been well documented. To date, however, there has been a paucity of research on the effects of dysphagia following HNC on carers, independent of the consequences of a gastrostomy. The objective of this qualitative study was to report on the experiences of carers of people with dysphagia (non-gastrostomy dependent) following nonsurgical treatment for HNC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(146 citation statements)
references
References 23 publications
11
135
0
Order By: Relevance
“…HNC survivor and carer participant details with maximum variation sampling parameters and additional demographic details are reported in Table 1. [Insert Table 1 near here] Please note all of the HNC survivors and seven carers within this study were involved in the larger project surrounding mealtime difficulties that may arise from HNC and its treatment which have been published elsewhere (Nund et al, 2014a, b, c).…”
Section: Carer Participantsmentioning
confidence: 99%
“…HNC survivor and carer participant details with maximum variation sampling parameters and additional demographic details are reported in Table 1. [Insert Table 1 near here] Please note all of the HNC survivors and seven carers within this study were involved in the larger project surrounding mealtime difficulties that may arise from HNC and its treatment which have been published elsewhere (Nund et al, 2014a, b, c).…”
Section: Carer Participantsmentioning
confidence: 99%
“…Healthcare professionals (especially nurses), hospitals, and families play a key role in reducing the problems of caregivers of PEG patients . The results of this study show that caregivers have demands they expect to be met by healthcare system and by nurses and family members during the care process.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has looked at eating-related difficulties during treatment, with evidence that chemosensory changes may resolve around 8 weeks after treatment ceases. An emergent body of qualitative research has identified how treatment and cancer can have long term impacts on the ability to 'eat well' long after treatments ceases [3][4][5][6][7][8][9][10][11][12]. review of qualitative literature found several consistent themes across studies that demonstrate a 'significant impact' on the experience of eating and changed meaning of food.…”
Section: Introductionmentioning
confidence: 99%